Quantum technology for development framework as a tool for science diplomacy - Mafu, Mhlambululi; Senekane, Makhamisa (Frontiers in Research Metrics and Analytics, 2023)
The state-of-the-art quantum technologies leverage the unique principles of quantum mechanics, which include quantization, uncertainty principle, interference, entanglement and decoherence, to produce useful devices and scientific advancements not possible with classical technologies. As a result, quantum technologies, in particular, offer specific advantages that make communications networks secure and unbreakable and devices with unprecedented levels of accuracy, responsiveness, reliability, scalability and efficiency than classical emerging technologies. These capabilities can contribute significantly to addressing energy, agriculture, climate change, national security, healthcare, education and economic growth challenges. Unfortunately, these developments in these areas have not been evenly distributed between the Global North and the Global South, inadvertently creating a societal and economic gap. Closing this gap is critical to creating a more inclusive and sustainable future for all, thus delivering key sustainable goals. Therefore, to close this gap, this article proposes a quantum diplomacy framework as a means to deliver science diplomacy. Moreover, we discuss how emerging quantum technologies could profoundly impact all seventeen United Nations Sustainable Development Goals. We consider this work a timely and vital intervention to prevent the gap from increasing.